Prevalence of lower limb venous disease in surgeons: a case study and results of a survey by the BAOMS Reconstruction Surgical Subspecialty Interest Group. Issue 7 (September 2021) - Falls, D.; Nugent, M.; Wilson, A.; Ho, M.
Abstract: We report a case of venous leg ulceration in a reconstructive oral and maxillofacial surgeon. An online survey was created by the British Association of Oral and Maxillofacial Surgeons (BAOMS) Reconstruction Surgical Subspecialty Interest Group (SSIG), primarily to target head and neck surgeons, to investigate the perceived risk and occurrence of venous leg disease. Two respondents had received treatment for lower limb venous disease thus compromising their ability to work, while 13 had symptoms of early venous disease. Our study shows an interesting area of concern for occupational health in surgeons, particularly in those carrying out long operations, as will be the case for members of the Reconstruction SSIG.